1964
DOI: 10.1172/jci104921
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Induction of Human Riboflavin Deficiency with Galactoflavin *

Abstract: Signs of riboflavin deficiency require many months to develop in patients placed on riboflavinrestricted diets (1-6). The demonstrations that riboflavin deficiency induced by dietary restriction or riboflavin antagonists resulted in regression of rodent tumors (7-13) prompted several efforts in this laboratory to produce riboflavin deficiency in patients with neoplastic disease (14, 15). Riboflavin antagonists were used in these studies with the objective of producing the deficiency state rapidly, since a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Consequently, hepatic iron contents were significantly reduced by riboflavin deficiency. Thus, riboflavin antagonists, such as galactoflavin (124), would be expected as a novel therapeutic agent for HIO, unlike other nutrients whose agonistic actions are desired therapeutically. However, there are contradictory studies on the effect of riboflavin on anemia (125)(126)(127).…”
Section: Riboflavinmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, hepatic iron contents were significantly reduced by riboflavin deficiency. Thus, riboflavin antagonists, such as galactoflavin (124), would be expected as a novel therapeutic agent for HIO, unlike other nutrients whose agonistic actions are desired therapeutically. However, there are contradictory studies on the effect of riboflavin on anemia (125)(126)(127).…”
Section: Riboflavinmentioning
confidence: 99%
“…Riboflavin deficiency was shown to reduce intestinal iron absorption and utilization, leading to anemia in humans and rats ( 123 , 124 ). Consequently, hepatic iron contents were significantly reduced by riboflavin deficiency.…”
Section: Prevention Of Iron-induced Liver Damage By Nutrientsmentioning
confidence: 99%
“…Riboflavin deficiency in human adults is known to result in low hemoglobin levels. When riboflavin deficiency was induced in human volunteers, the subjects got anemia, which was restored when riboflavin status was restored [34]. Studies in the Gambia have also shown that iron given with riboflavin supplements was more efficient in restoring hematologic parameters than iron given alone [35,36].…”
Section: Iron and Riboflavinmentioning
confidence: 99%
“…The objective signs of riboflavin deficiency include angular stomatitis, chielosis, seborrhoeic dermatitis, glossitis and visual changes (McLaren, 1982). In experimental deficiency, Lane et al . (1964) found that sore throat and angular stomatitis were usually the first symptoms to appear followed ultimately by hypoplastic anaemia and neuropathy (Alfrey & Lane, 1970).…”
Section: Diagnosismentioning
confidence: 99%